Quantification of Organophosphate and Carbamate residue on stored grains in Ondo State, Nigeria - Akinneye Joseph O; Adedolapo AO; Adesina Femi P (Journal of Biology and Medicine - Peertechz Publications, 2018)
Pesticides are beneficial in reducing the loss cause by insect infestation on grains but its toxicity and persistence in the environment is of health concern. Cereal grains preserved with insecticide are considered to be good for consumption if it's active content substances of insecticide do not exceed the maximum residue limits (MRLs). The objective of this research is to quantify the residue of chlorinated pesticide content of the four grain samples and compare their residues content with FAO/WHO MRLs. Dichlorvos was found in all the bean samples with quantities ranged from 0.06 - 0.212 ppm and there was no significant difference (p >0.05) between location 2 (0.08 ppm) and Location 3 (0.06 ppm). Likewise on rice, dichorvos was present in all locations, ranged from 0.04 to 0.37 ppm and its residues detected in each location were significantly different (p < 0.05) from one another. For wheat, carbaryl was detected in location 4 (0.21 ppm) only, likewise pirimiphos-methyl in location 2 (0.75 ppm). Carbofuran, malathion, chlorpyrifos and parathion were not detected in any of the maize samples. Pirimiphos-methyl had the highest concentration in the beans sample (0.5 ppm) and had the lowest concentration in rice (0.07 ppm). Wheat had the highest number of insecticide residue and followed by rice sample. Almost 99% of the pesticides monitored were below their MRL, while only chlorpyrifos concentration slightly exceeded its maximum residue limit in bean. Nevertheless, their detection further attests to their persistence and efforts should still be geared towards appropriate uses of pesticides.